Characterization of Zirconia- Hydroxyapatite Nanocomposites for Orthopedic and Dental Applications - Khahtan Sabree, Israa; Saleh Mahdi, Ola (International Journal of Engineering and Technology, 2018)
Zirconium oxide ceramic was proposed for different biomedical applications. It is used in orthopedic as hip and knee prostheses and in dentistry due to the good mechanical, biological high corrosion and wear resistance properties, addition to the aesthetic property owing to tooth like color. Zirconia stabilized with Y2O3 has the best properties for these applications. The present work aims to study the effect of (5 and 10)Wt.% hydroxyapatite (HA) as additives to 3 mol% yttria stabilized zirconia (3YSZ) nano powder matrix. The green body samples were shaped by powder technology using cold pressing then sintering at (1300 and 1400)áµ’C. The 3YSZ/ HA nanocomposites samples were characterized by XRD to investigate phase stability with varying percent's of HA and different sintering temperatures, the mechanical propertiesÂ (maximum bending strength and hardness) were investigated as a function of the HA content, the changes of the thermal expansion coefficient for composite samples were investigated using Dilatometer. The experimental results proved that additions of (5 and 10)Wt.% HA to 3YSZ matrix reduce both hardness and max. bending strength, while increasing sintering temperature from 1300áµ’C to 1400áµ’C leading to an increase in the hardness and bending strength for all composite samples. The results of thermal expansion test showed a reduction in the thermal expansion coefficient with presence of HA%, however the coefficient of 3YSZ/ 10%HA is closer to 3YSZ from 3YSZ/ 5%HA. EDS analysis shows improvement in the bioactivity of inert 3YSZ with HA% additions represented by increasing Ca and P ions on the composite samples after immersing in SBF for 6 days.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â